Cochlear Structure in the Dolphin, Lagenorhynchus obliquidens - Wever, Ernest Glen (1972)
The cochleas of five specimens of the Pacific white-sided dolphin, Lagenorhynchus obliquidens, that had been fixed by intravital perfusion, embedded in celloidin, and sectioned in a continuous series, were studied with particular attention to the numbers and distribution of hair cells and ganglion cells. The number of inner hair cells is estimated as 3272 and the number of outer hair cells is estimated as 12,899, for a total of 16,171 cells. The ganglion-cell population is estimated as 50,412 after correction for cell splitting in the sectioning process.